The Effect of the Use of Stories in Improving the Writing Ability of the Second Year Students of Madrasah Tsanawiyah Negeri Mangempang Barru - Syamsiah Syamsiah (Universitas Sulawesi Barat, 2017)
This research investigated the implementation of the use of stories in improving the students’ writing ability. The objectives of this research were (1) to find out whether or not the use of the stories is effective to improve the writing ability, (2) to find out which of the writing components that is mostly increased by the implementation of the use of stories. This research was carried out on the second year students of MTs N Mangempang Barru. The writer employed a quasi-experimental design. This research assigned two groups namely experimental and control group. Each group consists of 24 students. The sample was using cluster random sampling. The experiment group of were taught by using stories while in other group taught by using mono text. The instrument of this research was writing descriptive text. The data obtained through the test were analyzed by using inferential analysis by some formulas. Based on the result of research the mean score of post test of experimental group (73.42) was higher than the control group (69.50). The result of the t-test value (2.99) was higher than t-table value (2.021) . in other words, Ho was rejected and H1 was accepted..This means that the use of stories significantly improved the students’ writing ability of the second year students of MTs N Mangempang Barru.